RETRACTED: Research at the MSU Meteorological Observatory site in 2024 - Gagarin V.E.; Koshurnikov A.V.; Frolov D.M.; Nikolaeva E.S. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001